If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (15x)(15x) = (5x)(5x)(5x) Remove parenthesis around (15x) 15x(15x) = (5x)(5x)(5x) Remove parenthesis around (15x) 15x * 15x = (5x)(5x)(5x) Reorder the terms for easier multiplication: 15 * 15x * x = (5x)(5x)(5x) Multiply 15 * 15 225x * x = (5x)(5x)(5x) Multiply x * x 225x2 = (5x)(5x)(5x) Remove parenthesis around (5x) 225x2 = 5x(5x)(5x) Remove parenthesis around (5x) 225x2 = 5x * 5x(5x) Remove parenthesis around (5x) 225x2 = 5x * 5x * 5x Reorder the terms for easier multiplication: 225x2 = 5 * 5 * 5x * x * x Multiply 5 * 5 225x2 = 25 * 5x * x * x Multiply 25 * 5 225x2 = 125x * x * x Multiply x * x 225x2 = 125x2 * x Multiply x2 * x 225x2 = 125x3 Solving 225x2 = 125x3 Solving for variable 'x'. Combine like terms: 125x3 + -125x3 = 0 225x2 + -125x3 = 0 Factor out the Greatest Common Factor (GCF), '25x2'. 25x2(9 + -5x) = 0 Ignore the factor 25.Subproblem 1
Set the factor 'x2' equal to zero and attempt to solve: Simplifying x2 = 0 Solving x2 = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x2 = 0 Take the square root of each side: x = {0}Subproblem 2
Set the factor '(9 + -5x)' equal to zero and attempt to solve: Simplifying 9 + -5x = 0 Solving 9 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -5x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = 0 + -9 -5x = 0 + -9 Combine like terms: 0 + -9 = -9 -5x = -9 Divide each side by '-5'. x = 1.8 Simplifying x = 1.8Solution
x = {0, 1.8}
| 2.1y+6=10 | | x^3+2x^2-24x=0 | | v(v)-22v+21=0 | | s(s)+14s+48=0 | | (2x)(2x)=(2x+4)(2x+4)-(x+1)(x+1) | | 5x^2-51x+10=0 | | (2x)(2x)=(2x+4)(2x+4)-9x | | 1-2x=33 | | 1/3=2x | | 1/3=2 | | c+9=2 | | 1.3-3n=8 | | 1-4x=33 | | 6x-8=46 | | (-0.4)= | | (5)2x=(10)1x | | 12r^2-42r+972=0 | | 4(6-r)=32 | | 8x+15y=490 | | 6v+x=2 | | x+6y=2v | | x^2+28x-96=0 | | a^2+b^2=0 | | 3(4z-1)-3(z+9)=2(z+1) | | 3(4z-1)-3(z+9)=5(z+1) | | (8x^2-2x)=(x^3-8x+5) | | 3(4z-1)-3(z+1)=2(z+1) | | (X+3)(X^2+5X-6)= | | -3x^2(4x^2+5)= | | 2Y-33= | | 2Y-33=-9Y | | 9y^2+29y-28=0 |